Using femtosecond laser processing quartz glass microchannel sample cell. Issue 9 (15th May 2019) - Wang, Fubin; Liu, Mengzhu; Huo, Xiaotong; Chen, Lei; Chen, Jianxiong
Abstract: To improve the intensity and reliability of the emission fluorescence spectrum signal of petroleum pollutant samples, we designed multiple microchannel sample pools to replace traditional sample pool with square section. First, the microchannel structure of the sample pool was designed. Second, we analyzed the pulse intensity distribution and laser ablation volume (LAV) of a femtosecond laser. Then, based on the LAV, we tested the oblique motion of the laser focus at a 45° angle combined with the change in laser power, ablated a specific length region on the quartz glass surface, and indirectly determined the processed depth of the hole inside the quartz glass. Finally, using quartz glasses of 2, 5, and 10 mm in thickness as substrates, we separately varied the processing speed in the x‐direction, feed rate in the y‐direction, and laser output power of the laser processing platform, and obtained the shape‐structure of the microchannel inside the quartz glass under different processing parameter combinations. The experimental results demonstrate that the proposed method is effective at processing a specific hole depth inside the quartz glass. Experiments show that the sample cell can be used for comparative detection of fluorescence signals.